Разработка метода оценки качества инфраструктуры предприятия и ее компонентов - Левыкин, В. М.; Юрьев, И. А. (My University, 2016)
Одним з актуальних, проте недостатньо висвітлених у науковій літературі питань є розробка методу оцінки якості функціонування інфраструктури підприємства. Запропоновано метод розрахунку комплексної оцінки якості інфраструктури підприємства на основі використання якісних і кількісних показників. Для проведення якісної оцінки інфраструктури підприємства запропоновано використовувати лінгвістичну шкалу. Кількісну оцінку пропонується здійснювати на основі витрат, пов’язаних із підтримкою інфраструктури підприємства. Effective and sustainable development of the company, requires the appropriate infrastructure. Functioning of the process of enterprise infrastructure management is impossible without a comprehensive assessment of its effectiveness. Determine the quality of the infrastructure of the enterprise possible in solving two interrelated objectives: establishing a baseline, reflecting the processes and results of infrastructural maintenance of enterprise; selection and justification of a set of indicators to measure the impact of infrastructural maintenance of enterprise. In this regard, relevant is studying of the effectiveness of the enterprise infrastructure over time, in order to obtain full information about its condition. This information can be used for the development of rational management decisions on the development and improvement of the enterprise infrastructure.
Keywords: инфраструктура; комплексная оценка; качественная оценка; количественная оценка